2016
DOI: 10.1101/040238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Y-box protein 1 is required to sort microRNAs into exosomes in cells and in a cell-free reaction

Abstract: Exosomes are small vesicles that are secreted from metazoan cells and may convey selected membrane proteins and small RNAs to target cells for the control of cell migration, development and metastasis. To study the mechanisms of RNA packaging into exosomes, we devised a purification scheme based on the membrane marker CD63 to isolate a single exosome species secreted from HEK293T cells. Using immunoisolated CD63-containing exosomes we identified a set of miRNAs that are highly enriched with respect to their ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 65 publications
2
31
0
Order By: Relevance
“…To specifically delve into the role of miRNAs within exosomes a reagent where the production of miRNA-containing exosomes can be specifically blocked in vivo is needed. As we begin to identify factors involved in miRNA loading, such as Ybx1, hnRNPA2B1, and SYNCRIP (4446), novel mouse strains can be created to address these questions. Furthermore, the production of exosomes containing only the miRNA of interest would make a strong tool both for further understanding of that miRNA within exosomes and for therapeutic applications down the road.…”
Section: Discussionmentioning
confidence: 99%
“…To specifically delve into the role of miRNAs within exosomes a reagent where the production of miRNA-containing exosomes can be specifically blocked in vivo is needed. As we begin to identify factors involved in miRNA loading, such as Ybx1, hnRNPA2B1, and SYNCRIP (4446), novel mouse strains can be created to address these questions. Furthermore, the production of exosomes containing only the miRNA of interest would make a strong tool both for further understanding of that miRNA within exosomes and for therapeutic applications down the road.…”
Section: Discussionmentioning
confidence: 99%
“…Some RBPs can guide transport to specific cellular areas, and – as has been recently shown in animal cells – facilitate RNA export from cells and over long distances (Hematy et al ., ; Shurtleff et al ., ). Concerning long‐distance mobility of RNAs in plants, the co‐occurrence of different RNAs and several RBPs in phloem samples suggests their involvement in conferring RNA stability and mobility.…”
Section: Mode Of Rna Transportmentioning
confidence: 97%
“…A second study reported that, alternatively, tRFs might function in analogy to miRNAs, i.e., by binding to the 3 ′ UTR of mRNAs, inhibiting the expression of RPA1 mRNA (Maute et al 2013). Recent reports imply that YBX1 is required for loading of various RNA species, including tRFs, into exosomes (Shurtleff et al 2016). Some studies have reported that YBX1 binds to several RNAs like tRNA fragments and miRNAs (Blenkiron et al 2013;Goodarzi et al 2015;Liu et al 2015).…”
Section: Leumentioning
confidence: 99%